Testing framework for investigating learning outcome from quiz game: a study from Macedonia and Norway - Videnovik, Maja; Kiønig, Linda; Vold, Tone; Trajkovik, Vladimir (IEEE, 2018)
This electronic document is a “live” template and already defines the components of your paper [title, text, heads, etc.] The quiz-game Kahoot! is a Norwegian developed quiz game that is used in all countries in the world. At the Inland University of Applied Sciences, Kahoot! has been played in several classes and in different ways. This paper will present research at the elementary level both in Macedonia and in Norway. The research is based on an adapted version of the Education Games Evaluation Framework. The adaption is mainly due to it not being a computer game, but a quiz game. The framework for testing the learning outcome from games is based on factors that influence on students Quality of Experience, while playing the game, game’s ease of use, usefulness, educational value of the game, adoption of the game to the curricula, and teachers’ opinion concerning using the game in the learning process. The purpose of the educational games evaluation framework guideline is to identify different parameters that influence on qualitative integration of educational games in the classroom and investigate their interconnections. The parameters refer to students' attitudes, opinions and interactions during the game. Game's ease of use is a factor that determines students’ motivation for using the game for learning. We also took into account the use of a game for achieving educational goals (not only as an assessment method). In that way we tried to make a correlation between entertainment and educational value of a game. The evaluation guideline provides the way to create questionnaires for educational games evaluation. This evaluation framework guideline was used to evaluate several educational games available on market (e.g. ScottieGo) and prototypes (e,g, ZookKemon Go). For the quiz game the adjustments have been to reduce the number of questions regarding the specific gaming questions and rather add questions that are directed directly towards the quiz game. The pupils at the elementary school have played Kahoot! both in Macedonia and in Norway in order to support the learning outcome from the lectures. The teachers use it as a way of both breaking up the lectures, and to test the pupils. The learning from the quiz game has been discussed. There is an ongoing investigation regarding Kahoot! supporting deep or surface learning. The preliminary results are pointing towards surface learning rather than deep learning. However, the activity of performing a quiz game can have a value in itself. It breaks up the lecture and used as an indicator of what the pupils have learned, it can be perceived as both fun and educational by the pupils. A quiz game can thus be used to boost reflection processes. The pupils will have little time to reflect, but they will still have to recall what they think is the answer. These reflections can also contribute towards the learning outcome. For this paper, we have focused on if the pupils perceive playing the quiz game as fun. We have asked if they have had fun competing, if they have had fun playing it with their class mates, if they are motivated to learn when using the quiz game, if they learn something from the gaming and if they would like to continue playing the quiz game in class. Keeping in mind that these are pupils in elementary school, we suggest that these questions from the quantitative survey would provide us with data that would answer our questions: “do pupils find it fun to play (quiz) games in class?” and “does the gaming contribute to a perceived learning outcome”.
Keywords: Quiz game learning; games for learning; kahooting; game evaluation framework